Properties of wood from 7-year-old Cedrela odorata trees of two different populations growing in agroforestry systems with Theobroma cacao - Rigg-Aguilar, Priscilla; Moya Roque, Róger (Instituto de Ecología, A.C., 2018)
This study evaluated the properties of juvenile wood from 7-year-old Cedrela odorata trees in two populations with the same provenance and planted in an agroforestry system with Theobroma cacao (cacao). The morphological characteristics (diameter at breast height; heartwood, sapwood, bark, and pith percentages; and eccentricity of pith), physical properties (shrinkage, green moisture content, green density, and specific gravity) and mechanical properties (modulus of rupture (MOR) and modulus of elasticity (MOE) in bending, compression stress, Janka hardness, tension stress and shear stress) were determined between two populations. The variation of the physical properties and morphological characteristics at different tree heights was also evaluated. The results showed that there were differences in both populations in terms of bark, pith, volumetric shrinkage, green moisture content, green density, MOR and MOE in bending, longitudinal compression and perpendicular tension. The results showed that population 2 presents better characteristics of growth and quality of wood for structural and furniture uses; hence, this population planted in agroforestry systems has good plantation conditions and wood quality.